Digitisation and analysis of historical vertical deflections in India. Issue 390 (4th May 2023) - Featherstone, W. E.; Goyal, R.
Abstract : We describe the [somewhat tedious] process of digitising from a 1955 report that lists over 1000 vertical deflections in India and some surrounding countries. It involved error-checking with closed-loop tests and resolution of an ambiguity surrounding the meridional vertical deflection at the Kalianpur origin of the datum. We transformed these Kalianpur coordinates to geodetic coordinates on geocentric datum to compute absolute vertical deflections. However, due to many changes to the Everest spheroid due to different feet to metre conversions and readjustments of the Kalianpur datum, we were restricted to using the abridged Molodensky transformation parameters for the 1975 Kalianpur datum and Everest 1956 spheroid based on only seven common points from the WGS84 technical manual. We compared these transformed absolute vertical deflections with EGM2008 and GGMplus (for both models: meridional standard deviation: ∼±2″; prime vertical standard deviation: ∼±3″), showing that the effort of digitisation and scrutiny of historical geodetic data is indeed worthwhile.